2016
DOI: 10.3390/ma9030187
|View full text |Cite
|
Sign up to set email alerts
|

PEEK Primary Crowns with Cobalt-Chromium, Zirconia and Galvanic Secondary Crowns with Different Tapers—A Comparison of Retention Forces

Abstract: In prosthetic dentistry, double crown systems have proved their suitability as retainers for removable partial dentures. However, investigations in this context, regarding polyetheretherketone, are scarce. Therefore, the aim of this study was to test the retention force (RF) between polyetheretherketone (PEEK) primary and cobalt-chromium (CoCr), zirconia (ZrO2) and galvanic (GAL) secondary crowns with three different tapers. Primary PEEK-crowns were milled with the tapers 0°, 1°, and 2° (n = 10/taper, respecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(49 citation statements)
references
References 23 publications
1
46
1
1
Order By: Relevance
“…The possible explanation may be that known recommendation not to polish inner surfaces of PEEK crowns contributes to an initial high abrasiveness and consequently robust initial retentive force values. In addition to that, PEEK as a flexible material undergoes the process of better adaptation to the primary coping [9,10,11]. The results concerning the second hypothesis showed that final pull-off forces were 4.1 N and 3 N, respectively for each group.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…The possible explanation may be that known recommendation not to polish inner surfaces of PEEK crowns contributes to an initial high abrasiveness and consequently robust initial retentive force values. In addition to that, PEEK as a flexible material undergoes the process of better adaptation to the primary coping [9,10,11]. The results concerning the second hypothesis showed that final pull-off forces were 4.1 N and 3 N, respectively for each group.…”
Section: Discussionmentioning
confidence: 92%
“…The primary crowns were polished with a special bur kit for zirconia (sets 4430 and 4431, Komet Dental Gebr. Brasseler GmbH & Co. KG, Lemgo, Germany) with water cooling using a hand piece [9].…”
Section: Primary and Secondary Crowns Fabricationmentioning
confidence: 99%
“…After initial titles and abstracts screening , 701 irrelevant articles were excluded and a total of 41 articles were selected for full-text screening, 2 additional articles were found through hand searching [4,5] . After full text screening, 15 articles [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] were included in the present analysis.…”
Section: Results:-mentioning
confidence: 99%
“…Telescopic crowns on implants are effective in prosthesis stabilization with regard to horizontal forces in cases of advanced atrophy of the alveolar crest [4,19] . It was revealed that the variation in the results is not only material related, but also related to the manufacturing techniques [4] .…”
Section: Mansour S Et Almentioning
confidence: 99%
See 1 more Smart Citation